Answer:
might wanna take a picture instead...
Answer:
B. f(x) = -x + 11
Step-by-step explanation:
First if you rearrange the equation you get f(x) = -x + 11, like this:
x + y = 11
Minus x from both sides
y = -x + 11
F(x) and y are interchangeable so we just put f(x) in
f(x) = -x + 11
Each of the graphs are attached and we see that they are the same!
<em>Hope this helps!!</em>
<em>- Kay</em>
Answer:
f'(9) = 6
Step-by-step explanation:
f(x) = 6x+7
The derivative is
f'(x) = 6
Evaluated at x=9
f'(9) = 6
<span>x + 1/2 = 3/4
</span><span>x + 2/4 = 3/4
x = 3/4 - 2/4
x = 1/4
answer
</span><span>x = 1/4</span>